Ideologies in World Politics - Giesen, Klaus-Gerd.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2020)
Political ideologies shape the behaviour of states, international institutions, terrorist groups, political elites, non-governmental organisations, and other international actors. The book analyses how the most important of them affect today s world politics, and contribute to build a new and complex world order. The editor Dr. Klaus-Gerd Giesen is Professor of Political Science at Université Clermont Auvergne, France.
Introduction : Ideologies in World Politics -- Islam and Ideology in World Politics -- Humanitarianism and the Migration Crisis -- Ideology and International Security -- Environmental Ideologies in Global Politics -- The Ideology of the Global Commons -- Revisiting and Revising World-Wide Neoliberalism -- Exportism as an ideology in world politics -- The Transhumanist Ideology and the International Political Economy of the Fourth Industrial Revolution -- The Global Uprising of Populist Conservatism and the Case of Brazil -- Postliberalism in International Affairs.
Keywords: International relations; Political economy; Security, International; Comparative politics; International Relations Theory; International Political Economy; International Security Studies; Comparative Politics